IMPACT OF BILIARY TRACT INFECTION ON LIVER TRANSPLANT OUTCOMES - Dr. Muhammad Akram; Dr. Sayed Hasnain Abbas; Dr. Syeda Munazza Zafar; Dr. Muhammad Umar; Dr. Bilal Ahmed; Dr. Hafiz Bilal; Dr. Azam Shoaib; Dr. Abdul Ghafar; Dr. Shams Zehri; Dr. Abdul Wahab Dogar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: BTIs are frequent events in the post-liver transplant environment and are universally pathological for both the graft and the patient. The purpose of this paper is to compare the relationship that may exist between BTIs and liver transplant recipients with respect to graft survival, the chances of incidence of complications and the number of days the patient has to spend in the hospital. Objectives: To establish the overall certainty level of the observed biliary tract infection and its impact on other parameters like graft failure, length of stay at the hospital, and rate of graft rejection in the overall grafts. Materials and Methods: A retrospective study of 1,085 liver transplant recipients at Pir Abdul Qadir Shah Jilani Institute of Medical Sciences, from September 2018 to August 2024. Results: BTIs were found in 14% of the enrolled patients. Patients who had received BTIs were found to stay in hospitals for a longer time (28 days against 14 days), experienced higher graft failure (18% against 4%) as well as graft rejection (25% against 10%) rates. Conclusion: BTIs are directly related to the status of liver transplantation, and efforts should be made to improve the early diagnosis and treatment to enhance the survival rate of patients and grafts.